Full- Discrete Petrov Weak Galerkin Finite Element Method for Solving Coupled Burgers’ Problem - Maryam Mohammed Shnawa; Hashim A Kashkool (Zeta Repository, 2023)
In this paper, we introduce full- discrete Petrov weak Galerkin finite element method (PWG-FEM) for solving coupled Burgers’ equations in two dimensions. The slicing in the full-discrete Petrov weak Galerkin finite element method (FDPWG-FEM) is done for both space and time. The backward Euler method is used to approximate the time derivative method with (PWG-FEM).